Status of Thyroid Hormone Parameters in Hypertensive Disorders of Pregnancy - Singh, Amit; Singh, Samir (Nepalese Medical Journal, 2020)
Introduction: Hypertensive disorders of pregnancy (HDP) are the most common complications observed during pregnancy and are a leading cause of maternal and perinatal morbidity and mortality. Thyroid hormone abnormalities are prevalent in females of reproductive age group. However, the relation between thyroid hormones and hypertensive pregnant women remains unclear. This study aims to assess the status of thyroid hormone abnormalities in patients with HDP. Materials and Methods: This is a case-control study conducted for one year in Karnali Province Hospital and Deuti Hospital, Surkhet, Nepal. Thirty hypertensive patients with singleton pregnancies in the third trimester were taken as case and 30 healthy normotensive singleton pregnant women as control and their thyroid hormone parameters were compared. Statistical analysis was done using SPSS version 21. Results: The mean gestational age of recruited study subjects and control were 37.00 ± 3.04 weeks and 35.70±3.83 weeks (p>0.05). The mean value of TSH was significantly higher (p<0.05) in hypertensive subjects (4.19±2.95) μIU/L when compared with the control (2.67±1.71) μIU/L. There was no significant difference when the serum level of FT3 and FT4 were compared between hypertensive and normotensive pregnant women (p>0.05). Subclinical hypothyroidism was found in 16.66% of hypertensive subjects. Conclusions: HDP is associated with thyroid hormone abnormalities. An increase in TSH levels with normal FT3 and FT4 levels were found to be the most common form of thyroid dysfunction during pregnancy.